Effect of silane coupling agent and concentration on fracture toughness and water sorption behaviour of fibre-reinforced dental composites. Issue 4 (April 2023) - Thadathil Varghese, Jerrin; Cho, Kiho; Raju,; Farrar, Paul; Prentice, Leon; Prusty, B. Gangadhara
Abstract: Objectives: This paper presents the effect of silane treatment of S-2 Glass fibres on the fracture toughness and water sorption/solubility behaviour of fibre-reinforced flowable dental composites. The effect of epoxy- and methacrylate-based silane coupling agents (SCAs) on the mechanical strength and hydrolytic properties were investigated. The concentration of the selected SCAs on the mechanical and physical properties were investigated. The influence of molecular structure and concentration in the interfacial adhesion at the fibre-matrix interfaces was also studied. Methods: Short S-2 Glass fibres of 250 µm in length and 5 µm in diameter were etched with acid to remove any impurities and roughen the surface. The acid-etched fibres were silane treated with 3MPS, 3GPS, and 8MOTS at different concentrations by weight (%). The silane-treated fibres were incorporated at 5 % into the dental resin mixture. Untreated fibres were added at 5 % to the dental resin mixture and served as the control group. The physical properties such as water sorption, solubility, and desorption along with mechanical properties such as fracture toughness and total fracture work of the fibre-reinforced dental composites grafted with the above-mentioned SCAs were evaluated. The surface morphology of the fractured surface was studied and analysed. Results: The fracture toughness tests showed that the dental composites grafted with optimum weight per cent (wt. %) concentration of the SCA had a better stress intensity factor ( K IC ) when compared to the 2.0 wt. % and 3.0 wt. % concentration. The K IC value of dental composites grafted with untreated surface etched glass fibres was less than the K IC values of dental composites grafted with optimum concentrations of 3MPS, 3GPS, and 8MOTS by 81.6 %, 38.6 %, and 110.5 %, respectively. A similar trend was found while investigating the total work of fracture of the dental composites, between optimum concentration, 2.0 wt. % and 3.0 wt. % concentration of respective SCA. The increase in silane concentration also led to an increase in the water sorption/solubility characteristics. The absorption of water was most severe in the fibre-reinforced dental composites without silane treatment (32.9 µg/mm 3 ). The ANOVA results showed that the fibre-reinforced dental composites grafted with 8MOTS at optimum concentration showed an increase in fracture toughness when compared to optimum concentrations of 3GPS and 3MPS by 51.9 % and 15.9 %, respectively. The enhanced mechanical and physical characteristics are due to the increased adhesion between the fibre and silane achieved from the optimum wt. % concentration of 8MOTS. Similarly, dental composites grafted with 8MOTS at optimum concentration showed a decrease in water sorption characteristics when compared to optimum concentrations of 3GPS and 3MPS by 18.2 % and 0.6 %, respectively. The decreased water sorption characteristics at the optimum concentration of 8MOTS could be due to the reduced availability of reactive hydroxyl groups and the hydrophobic characteristics of 8MOTS. Significance: Silane coupling agents (SCAs) are important components of dental composites. The type and concentration of SCA have a significant effect on material properties. The current study focuses on understanding the effects of different SCAs and wt. % concentrations on the interfacial fracture behaviour and the influence of different SCAs on the water sorption and solubility behaviour of S-2 Glass fibre-reinforced flowable dental composites. Graphical abstract: ga1 Highlights: In-depth investigation of silane treatment on short S-2 Glass fibre. Study the effects of varying concentration (wt. %) of three distinct types of SCA on interfacial and hydrolytic behaviour. The fracture toughness study revealed the optimum concentration of SCAs intensifies the fibre/resin interfacial bonding. Morphology analysis verified that the optimum concentrations of SCAs resulted in cohesive failures at the interface. Water sorption investigation showed that the optimum concentration of SCAs resulted in the least sorption and solubility.